2000
DOI: 10.1037/0022-3514.78.2.273
|View full text |Cite
|
Sign up to set email alerts
|

Couples' shared participation in novel and arousing activities and experienced relationship quality.

Abstract: Using a newspaper questionnaire, a door-to-door survey, and 3 laboratory experiments, the authors examined a proposed effect of shared participation in novel and arousing activities on experienced relationship quality. The questionnaire and survey studies found predicted correlations of reported shared "exciting" activities and relationship satisfaction plus their predicted mediation by relationship boredom. In all 3 experiments, the authors found predicted greater increases in experienced relationship quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
508
5
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 513 publications
(543 citation statements)
references
References 50 publications
24
508
5
6
Order By: Relevance
“…While SEM does not go into detail about the cognitive mechanisms through which another person is assimilated to the self, research stemming from the model has identified factors associated with self-expansion. For example, shared experiences that are novel (Aron, Norman, Aron, McKenna, & Heyman, 2000), humorous (Fraley & Aron, 2004) or defined by mutual self-disclosure (Aron, Melinat, Aron, et al, 1997) are all associated with greater interpersonal closeness. What these studies have in common is that factors that lead to increased feelings of closeness are those that increase the perception of uniquely shared knowledge and experiences.…”
Section: Accepted Manuscript Cognitive Consequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…While SEM does not go into detail about the cognitive mechanisms through which another person is assimilated to the self, research stemming from the model has identified factors associated with self-expansion. For example, shared experiences that are novel (Aron, Norman, Aron, McKenna, & Heyman, 2000), humorous (Fraley & Aron, 2004) or defined by mutual self-disclosure (Aron, Melinat, Aron, et al, 1997) are all associated with greater interpersonal closeness. What these studies have in common is that factors that lead to increased feelings of closeness are those that increase the perception of uniquely shared knowledge and experiences.…”
Section: Accepted Manuscript Cognitive Consequencesmentioning
confidence: 99%
“…Why does uniquely shared experience generate interpersonal closeness, whereas more mundane or commonplace experiences do not (Aron et al, 2000)? One possibility is that awareness that a shared experience is unique creates a category boundary.…”
Section: Accepted Manuscript Cognitive Consequencesmentioning
confidence: 99%
“…Thus, one's partner who was instrumental to realizing their dream life may be viewed as dull because s/he does not seem to be serving goal striving. The well-known benefits for relationships of engaging in novel, exciting activities (Aron, Norman, Aron, McKenna, & Heyman, 2000) may emerge, at least in part, because such activities provide an avenue for partners to serve as means to shared goals. Thus, it is important that one's partner is instrumental to the goals of the moment in order to maintain interpersonal closeness and relationship satisfaction.…”
Section: Relationship Initiation and Evaluationmentioning
confidence: 99%
“…They may be preoccupied with thoughts about their partner during the periods just before and just after seeing each other in person, because the visit allows them to anticipate the reunion and then to relive and savor their experiences afterwards (Sahlstein, 2004). Novelty is an important part of what makes long-distance relationships thrive, and the loss of novelty and variety has been found to be associated with relationship dissolution when the relationship changes from long-distance to proximal (Aron et al, 2000;Stafford, Merolla, & Castle, 2006). This suggests that efforts to inject more novelty and variety into a relationship may help improve relationship quality.…”
Section: Long-distance Relationshipsmentioning
confidence: 99%
“…In two correlational studies, Aron and his colleagues found that participating in novel and exciting activities is associated with higher relationship satisfaction (Aron, Norman, Aron, McKenna, & Heyman, 2000, Studies 1 & 2). Moreover, in experimental studies, they found that couples assigned to participate in novel and 4 K. Jacobs Bao and S. Lyubomirsky arousing activities experienced increases in relationship satisfaction and passionate love (Studies 3 & 4).…”
Section: Variety Is the Spice Of Relationshipsmentioning
confidence: 99%